(untitled) (Bangladesh Heart Journal, 2020)
Coronary artery stent infection has been reported with both bare metal stent and drug eluting stent and can present as mycotic coronary artery aneurysm, pseudoaneurysm. myocardial abscess, pericarditis or exudative effusion. Infection at the site of coronary stent implantation is rare and is believed to result typically from either direct stent contamination at the time of delivery or transient bacteraemia from access site. Recently, several case reports of pseudoaneurysm formation after DES implantation have been reported in the literature. We describe the successful surgical management of giant mycotic pseudoaneurysm of RCA presenting as fever of unknown origin with AMI (inferior) three months after multivessel PCI in LAD & RCA with DES in radial route. This report illustrates the importance of early detection and prompt management of these rare coronary pseudoaneurysms, which is a highly lethal condition. At three months follow-up after surgery, the patient was asymptomatic with fair LVEF 58% Bangladesh Heart Journal 2020; 35(1) : 66-70